2015
DOI: 10.1093/nutrit/nuv025
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of evidence to support the theory of psychobiotics

Abstract: More trials are necessary before any inferences can be made about the efficacy of probiotics in mental health applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 54 publications
1
61
0
3
Order By: Relevance
“…Our findings follow another recent systematic review on the psychological benefits of probiotic supplementation [68]. Our review differs, notably, with the inclusion of six studies [33-A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 19 35,37,39,42] not included in the prior review, published after the prior review was undertaken.…”
Section: Accepted Manuscriptmentioning
confidence: 60%
“…Our findings follow another recent systematic review on the psychological benefits of probiotic supplementation [68]. Our review differs, notably, with the inclusion of six studies [33-A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 19 35,37,39,42] not included in the prior review, published after the prior review was undertaken.…”
Section: Accepted Manuscriptmentioning
confidence: 60%
“…However, a recent systematic review of psychiatric benefits of probiotics in humans found little evidence of positive outcomes [121], a finding running counter to the general optimism. Others have stated that the field, though not ‘faecal phrenology’, will ultimately be unable to provide true translational value without rigorous elucidation of mechanisms [122].…”
Section: Future Directions and Psychobiotics Beyond Prebiotics And Prmentioning
confidence: 86%
“…To date, there are a few reviews on probiotic effects on infantile colic, which may reflect peripheral nervous system action, and one recent study reviewing only human studies. [64][65][66] Similarly, among the 56 RCTs so far which tested probiotics in adults with IBS that have or have not shown effects on peripheral (bowel) functions, 15 none have investigated whether any CNS effect was affected or improved. We identified studies applying probiotics as single-or multiple-strain preparations in animals and humans.…”
Section: Discussionmentioning
confidence: 99%